1989
DOI: 10.1002/app.1989.070381103
|View full text |Cite
|
Sign up to set email alerts
|

Compounding of cellulose fibers with polypropylene: Effect of fiber treatment on dispersion in the polymer matirx

Abstract: SynopsisThe compounding of Kraft pulp with polypropylene was studied using a laboratory highshear roller blender. Dispersion was characterized by measuring the size and number of agglomerates in a thin compression-molded sheet. The effects of parameters such as surface treatment and mixing conditions were investigated. It is shown that with a suitable treatment, better dispersion of fibers can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 0 publications
2
70
0
3
Order By: Relevance
“…Several cellulosic products and wastes such as shell flour, wood flour and pulp have been used as fillers in thermoplastics (Lightsey, 1983;Kokta, 1988;Maldas & Kokta, 1991). The influence of wood flour on the mechanical properties of polypropylene was studied by Raj et al (1989) and they found that the cost of material could be reduced without too much loss of elastic modulus. However, fibrous fillers are now gaining more importance over particulate fillers due to their high performance in mechanical properties.…”
Section: Sisal Fibre-reinforced Thermoplastic Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cellulosic products and wastes such as shell flour, wood flour and pulp have been used as fillers in thermoplastics (Lightsey, 1983;Kokta, 1988;Maldas & Kokta, 1991). The influence of wood flour on the mechanical properties of polypropylene was studied by Raj et al (1989) and they found that the cost of material could be reduced without too much loss of elastic modulus. However, fibrous fillers are now gaining more importance over particulate fillers due to their high performance in mechanical properties.…”
Section: Sisal Fibre-reinforced Thermoplastic Compositesmentioning
confidence: 99%
“…Wood fibres are nonabrasive so that relatively large concentrations of fibres can be incorporated into polyolefins without causing serious machine wear during mixing and processing. Raj & Kokta (1989) have studied the mechanical properties of wood fibre filled medium density polyethylene (MDPE) composites. They observed a significant increase in modulus with increase in filler content.…”
Section: Sisal Fibre-reinforced Thermoplastic Compositesmentioning
confidence: 99%
“…It is known to improve the compatibilization between the hydrophobic LDPE matrix and hydrophilic fibers without any covalent chemical bonds between them. Raj and Kokta [15] investigated the influence of using various dispersing aids (stearic acid and mineral oil) and a coupling agent (maleated ethylene) in cellulose fiber reinforced polypropylene composites. Both the tensile strength and modulus of the composites studied were found to increase with the fiber content when either strearic acid or mineral oil (1 wt% by weight of fiber) were added as processing aids during the compounding.…”
Section: Ldpe or Mldpe-based Compositesmentioning
confidence: 99%
“…The determination of the optimum amount of surfactant is essential for efficient treatment. Insufficient amount does not achieve the desired effect, while excessive quantities lead to processing problems as well as to the deterioration of the mechanical properties and appearance of the product [217,221]. The amount of bonded surfactant can be determined by simple techniques.…”
Section: Non-reactive Treatmentmentioning
confidence: 99%